JavaScript moving to ES2015 : explore and master modern JavaScript techniques with ES2015 in order to build large-scale web applications - Antani, Ved; Timms, Simon; Prusty, Narayan (Packt, 2016)
Module 1. Mastering JavaScript -- Module 2. Mastering JavaScript Design Patterns -- Module 3. Modern JavaScript Applications
Keywords: JavaScript; JavaScript (Computer program language); Electronic books